Animal Models in the Pathophysiology of Cystic Fibrosis - Semaniakou, Anna; Croll, Roger P.; Chappe, Valerie (Frontiers in Pharmacology, 2019)
Our understanding of the multiorgan pathology of cystic fibrosis (CF) has improved impressively during the last decades, but we still lack a full comprehension of the disease progression. Animal models have greatly contributed to the elucidation of specific mechanisms involved in CF pathophysiology and the development of new therapies. Soon after the cloning of the cystic fibrosis transmembrane conductance regulator (CFTR) gene in 1989, the first mouse model was generated and this model has dominated in vivo CF research ever since. Nonetheless, the failure of murine models to mirror human disease severity in the pancreas and lung has led to the generation of larger animal models such as pigs and ferrets. The following review presents and discusses data from the current animal models used in CF research.